Disclosure of HIV Status to Infected Children in South India: Perspectives of Caregivers. (30th October 2017) - Ekstrand, Maria L; Heylen, Elsa; Mehta, Kayur; Sanjeeva, G N; Shet, Anita
Abstract: This study was designed to examine the rates of HIV serostatus disclosure in a sample of HIV-infected children in the state of Karnataka in South India, their reactions to learning their HIV-positive status and the reasons for and barriers to disclosure from the point of view of their caregivers. We enrolled 233 HIV-infected children, aged 5–18 years and their caregivers between July 2011 and February 2013 at HIV clinics in three tertiary care centers. Caregiver interviews included information about demographic characteristics, medical history, type of disclosure to the child and other related factors, including disclosure barriers. Three quarters ( n  = 185) of the caregivers reported that there had been no disclosure to the child, 15.4% ( n  = 38) reported partial disclosure (e.g. telling the child he or she had a 'chronic illness') and only 9.7% ( n  = 24) reported full disclosure, at a mean age of 10.9 (SD: 2.5) years. Caregivers, who planned to disclose in the future, stated on average that 16 years would be the right age. Those who favored a later disclosure reported that they feared strong negative emotional reactions from the child ( p  = 0.03) and social isolation ( p  < 0.001) following disclosure. These results show that that the level of full disclosure is low among South Indian youth living with HIV, and that when disclosure occurs, it is most likely to be partial. The majority of children who learned their status had been informed by a health-care provider, possibly reflecting the difficulty for a caregiver of having this conversation. The caregivers reported multiple disadvantages of disclosure, mostly because of fears of stigma and discrimination. Despite some evidence from the literature that disclosure can have positive effects on a child's health, it is thus clear that we need to develop, implement and evaluate community-based stigma reduction programs to reduce the social barriers to disclosure.